A study on UiTM’s relationship with its East Coast Franchised Colleges / Yeop Hussin Bidin, Md Noh Abd Majid and Ibrahim Jusoh - Bidin, Yeop Hussin; Abd Majid, Md Noh; Jusoh, Ibrahim (2006)
The success of a franchised system depends on the extent of relationship between the collaborative partners. Efforts to consolidate the beneficial working relationship between UiTM and the franchised colleges are determined greatly by the support services, the amount of information disseminated to the colleges and the active participation in programs and activities organized jointly with UiTM. Majority of the respondents interviewed are quite satisfied with the relationship. However, the students tend to view highly on the support services and their accessibility to information provided by UiTM. Meanwhile, the staff considers active involvement in joint activities as important factor in establishing good relationship between the partnering organizations. There are no significant differences between the franchised colleges in the measurement of factors or conditions that influence relationship except for college participation in activities whereby the MARA Polytechnics in Pahang and Kelantan tend to view this variable highly in influencing relationship. The multiple regression analysis generally shows that information dissemination as the most significant factor that explains the variance in UiTM relationship followed by participation and support services respectively. It is therefore necessary for UiTM to improve its channel or avenues for disseminating information as well as encouraging more activities to be jointly organized with the franchised colleges and the formulation of better future relationship such as close monitoring and greater supervision and assistance.